STUDI ADSORPSI CONGO RED PADA KITOSAN BERBASIS SELONGSONG PUPA BLACK SOLDIER FLY - Linda Hevira (LPPM Universitas Mohammad Natsir Bukittinggi, 2026)
Pollution of liquid waste containing synthetic dyes is an environmental problem that is also relevant in the industrial and pharmaceutical laboratories. One of these dyes is Congo Red, which is stable, difficult to degrade, and has the potential to cause negative impacts on the aquatic environment. This study aims to produce the ability of chitosan which is generally synthesized from shrimp shells, this time synthesized from the pupa sheath of the Black Soldier Fly (Hermetia illucens). The adsorption test was carried out in batches with variations in pH, contact time, and initial concentration of the dye. Chitosan-BSF before and after absorbing Congo Red was characterized using FTIR and SEM-EDS. The results showed that the adsorption process was greatly influenced by the environmental pH and the pHPZC value of chitosan. The adsorption percentage increased at pH below pHPZC due to the electrostatic interaction between the chitosan surface which produces a positive signal and the Congo Red molecule which produces a negative signal. Contact time affected the rate of achieving adsorption equilibrium, while increasing the initial concentration tended to decrease the adsorption percentage. These results indicate that chitosan from Black Soldier Fly pupae casings has the potential to be an alternative adsorbent that has added value and is environmentally friendly and supports the principle of the desire for dye waste processing.